(untitled) (Analysis in Theory and Applications, 2022)
In this work, some new fixed point results for generalized Lipschitz mappings on generalized c-distance in cone b-metric spaces over Banach algebras are obtained, not acquiring the condition that the underlying cone should be normal or the mappings should be continuous. Furthermore, the existence and the uniqueness of the fixed point are proven for such mappings. These results greatly improve and generalize several well-known comparable results in the literature. Moreover, some examples and an application are given to support our new results.